Clinical evaluation of accessory nerve transfer for shoulder function restoration in upper root brachial plexus injuries - Phu, Ho Man Truong; Linh, Le Khanh; Nhan, Ho Van; Dat, Tran Thanh; Dung, Tran Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objective: Upper root injuries of the brachial plexus often lead to significant impairment in shoulder motor function, drastically reducing the quality of life for affected individuals. This study systematically evaluates the clinical efficacy of nerve transfer surgery, specifically the transfer of the accessory nerve to the suprascapular nerve, aimed at restoring shoulder function. Methods: This prospective study was conducted on 31 patients who sustained upper root brachial plexus injuries, treated with accessory nerve transfer to the suprascapular nerve at Hue Central Hospital from 01/2019 to 10/2022. Selection criteria included patients with complete paralysis in shoulder abduction and external rotation, with a surgery timeline of less than 12 months post-injury. Postoperative motor function recovery was monitored for at least 12 months. Results: Among the 31 patients, 58.1% achieved shoulder abduction strength at M3 or higher, with an average shoulder abduction range of motion increasing by 113 degrees after surgery. Similarly, 48.3% of patients achieved external shoulder rotation strength at M3 or higher, with an average external rotation range increasing by 21 degrees. No postoperative complications were recorded during the follow-up period. Conclusion: Accessory nerve transfer to the suprascapular nerve emerges as a safe and effective surgical intervention for restoring shoulder motor function in patients with upper root brachial plexus injuries. The procedure significantly enhances shoulder abduction and external rotation, thereby improving the overall quality of life for patients.